The Contribution of CO2 to Forest Regeneration After Nuclear Fallout – An Anthropometric Study - Pirot, Florent (European Journal of Applied Sciences, 2022)
The end of alpha emitters in fuels has changed the landscape in terms of how pollutants have to be defined. It is clear that car and industrial “emissions” have been typically condemned for the effects of alpha emitters (NORMs, etc.) in the fumes, CO2 serving as pretext. New car fuels without alpha emitters allow to show how CO2 makes a decisive contribution to the regeneration of forests through photosynthesis. These effects are made obvious through a series of small case studies analyzed thoroughly. The word “anthropometric” is used because it is shown as well that a crematory component in the nuclear fallout makes forest regeneration harder, because the dead human cells depositing on trees make photosynthesis more difficult for them. The case of sodium- mash is discussed as well and shown to be intermediary.